Analysis of The Differences of Purchasing Decision making style between male and female customers in Food Supplements products in Malang - Bhisma Maha Santika Haning Yudha; Gai Sin Liem (AIBPM Publisher, 2019)
Advertising is one form of integrated marketing communication where trust is an important factor in it. Advertising is one form of communication, and in general there are various factors that influence the delivery of information from one party to another in communication. Factors such as trust are very important in communicating products, so it is important for companies to find out how much trust of the customers to their products. This study aims to analyze the differences in advertising trust (consumer trust) on the advertising media used. The media studied in this research are social media and video advertising. The main objective of this research is to find out which platform is more reliable so that the company can save the budget and the company invests effectively and efficiently.